The effectiveness of interventions for improving the uptake of Intermittent Preventive Treatment (IPT) for malaria control among pregnant women in sub-saharan Africa: A systematic literature review - Chukwuma Ernest Egbujor; David Chinaecherem Innocent; Uchechukwu Madukaku Chukwuocha; Uzochukwu Godswill Ekeleme; John Chigozie Ekenze; Ugonma Winnie Dozie; Chiagoziem Ogazirilem Emerole; Igiri Vivian Chika; Nanush Damarlapally; Ihuoma Chimdimma Dike; Stanley Chinedu Eneh (Archives of Preventive Medicine - Peertechz Publications, 2023)
Background: Malaria in pregnancy is a public health problem in Sub-Saharan Africa (SSA) that continues to account for increased morbidity and mortality among women. Anemia, maternal death, stillbirth, and low birth weight are complications associated with malaria in pregnancy. Adoption of recommended malaria control measures such as intermittent preventive treatment (IPT) remains a problem among pregnant women in SSA. Aim: We aimed to evaluate the effectiveness of interventions for improving the uptake of IPT for malaria control among pregnant women in SSA. Methods: The MEDLINE, Pub-Med CINAHL, and African Journal Online databases were subjected to a systematic search for Randomized Control Trials (RCTs) for the review. The studies were screened for eligibility and evaluated for methodological quality using the Cochrane Risk of Bias Tool. The screening process was carried out by one reviewer to help reduce the amount of time and resources that would have been used by two reviewers. The narrative synthesis approach was adopted for data analysis and synthesis after extraction from selected studies. Results: A total of 1679 articles were found, and the comprehensive screening of the search results left a total of four RCT studies that were deemed eligible for inclusion in the review. All the included studies adopted two-arm comparisons, i.e., the control and intervention groups. The findings revealed that three studies evidently reported increased uptake of intermittent preventive treatment in pregnancy using sulfadoxine-pyrimethamine (IPTp-Sp) doses among pregnant women following community-based promotional activities. Conclusion: Our review revealed the effectiveness of community-based promotional activities as effective interventions for improving uptake and possibly compliance to intermittent preventive treatment in pregnancy (IPTp) and antenatal attendance. This evidence and findings will guide policy-makers and health agencies in the SSA region to plan further interventions.